Penerapan Metode (Oreste) Pada Sistem Pendukung Keputusan Dalam Pemilihan Kader Puskesmas Desa Pasar Pino - Rahayu, Reska Putri Rahayu; Yulianti, Liza; Fredricka, Jhoanne (MEANS (Media Informasi Analisa dan Sistem), 2023)
Health Center in Pasar Pino Village is the only health center in Pino Raya Sub- District of South Bengkulu Regency. The selection of cadre members in Pasar Pino Village was still done manually by filling out forms and resulted in a lot of fraud when selecting these cadres to get cadres who did not meet expectations in their field and resulted in many misunderstandings between the people of Pasar Pino Village. The application of the method (oreste) to a decision support system in the selection of cadres for the Health Center of Pasar Pino Village was made to assist the health center in facilitating the selection of good cadres and assisting in proper data processing in terms of storage. Based on the results of the tests that have been carried out, the functional oreste application for the selection of cadres for the Health Center of Pasar Pino Village is running as expected and the data processing of each prospective cadre is successfully input into the application by calculating the Besson rank value for each criterion, then determining the results of determining the cadres for the Health Center of Pasar Pino Village.